Adaptação hemodinâmica gestacional em candelas - de Almeida, Vívian Tavares [UNESP]; Uscategui, Ricardo Andres Ramirez [UNESP]; da Silva, Priscila Del Aguila [UNESP]; Avante, Michele Lopes [UNESP]; Simões, Ana Paula Rodrigues [UNESP]; Vicente, Wilter Ricardo Russiano [UNESP] (FapUNIFESP (SciELO), 2017)
Throughout pregnancy, maternal hemodynamic adaptation is needed to ensure proper uterine perfusion and fetal development. When the uteroplacental vascular system is formed, starting with reduced resistance to uterine arterial flow, this results in decreased total vascular resistance, an activation of neuroendocrine vasoactive peptides, an increase in circulating blood and changes in the cardiovascular system morphophysiology to respond to the increasing demands of uterine perfusion. There has been considerable study of hemodynamic adaptation in pregnant women and this assessment has become a diagnostic tool for fatal obstetric disorders. However, in bitches the available information in this regard is limited; therefore a parallel was drawn between other species of animals and women, in order to subsidize the paucity of information about this process and facilitate the understanding of maternal-fetal hemodynamic adaptation in pregnant bitches. This review and literature analysis aimed\ to discuss morphophysiological cardiovascular adaptations during pregnancy and the possible disorders that can affect this process in pregnant female dogs.
Hemodynamic gestational adaptation in bitches
Keywords: Cardiovascular; Dogs; Gestation; Morphophysiology; Pregnancy